Metabolic acidosis as a risk factor for bronchopulmonary dysplasia in preterm infants born between 23 + 0 and 31 + 6 weeks of gestation: a retrospective case-control study - Shin, T. W.; Lee, E. J.; Choi, H. W.; Yoo, Y. M. (Frontiers in Pediatrics, 2025)
BackgroundMetabolic acidosis is a common condition in preterm infants; however, its independent role in the development of bronchopulmonary dysplasia (BPD) remains unclear. In this study, we examined the association between metabolic acidosis and the occurrence of moderate/severe BPD or mortality in preterm infants born between 23 + 0 and 31 + 6 weeks of gestation.MethodsWe retrospectively reviewed the medical records of 254 preterm infants (<32 weeks gestation) admitted between January 2017 and December 2024. The primary outcome was moderate/severe BPD or mortality before 36 weeks of postmenstrual age. Blood gas parameters, including pH, base excess, bicarbonate, and lactate, were analyzed daily during the first 14 days of life. Inverse probability of treatment weighting (IPTW) was applied to adjust for confounders such as gestational age, fluid balance, respiratory support, and patent ductus arteriosus (PDA) status.ResultsAfter excluding infants with missing data (n = 88), 168 infants were included, of whom 55 developed moderate/severe BPD or died. Following IPTW adjustment, metabolic acidosis on day 6 of life (DOL 6) was significantly associated with moderate/severe BPD or mortality (OR: 1.369, 95% CI: 1.085–1.727). Differences in cumulative fluid intake were statistically significant during the first week (7.365% vs. 23.478%, p = 0.022) and became more pronounced in the second week after IPTW adjustment (8.206% vs. 22.888%, p = 0.024).ConclusionMetabolic acidosis on DOL 6 was associated with an increased risk of moderate/severe BPD or mortality, suggesting its potential role as a modifiable risk factor. While excessive fluid intake has been linked to BPD, our findings highlight the complexity of fluid management in preterm infants. Further research is needed to determine whether correcting metabolic acidosis could improve respiratory outcomes.